SURVEY TENTANG PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 1 WONOAYU - ERA DWI LATIFAH (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
This research aims to determine the learning media being used and the reason for the use of learning materials as well as the feasibility of the learning media use on Economic subjects Accounting material grade XI IPS in SMA Negeri 1 Wonoayu. This type of research is descriptive research. The subject of research is the research object and Accounting teacher is teaching material used in the study of subjects in accounting class XI IPS and the instruments used are pieces of interviews and questionnaires, while media experts study the technique of collecting data using interviews, questionnaires and documentation study media experts. The research note that the medium used on subjects accounting is powerpoint. The reason the media used powerpoint to support the delivery of the material in the form of accounting theory and make use of the existing facilities at the school. As for the results of the feasibility, powerpoint media used on Economic subjects Accounting material grade XI IPS in SMA Negeri 1 Wonoayu is worth. Keywords: Learning Media, Descriptive Research, Services Companies Accounting Cycle.